Paediatric-onset lymphomatoid papulosis: results of a multicentre retrospective cohort study on behalf of the EORTC Cutaneous Lymphoma Tumours Group (CLTG) - Blanchard, Maël; Morren, Marie-Anne; Busschots, Anne-Marie; Hauben, Esther; Alberti-Violetti, Silvia; Berti, Emilio; Avallone, Gianluca; Tavoletti, Gianluca; Panzone, Michele; Quaglino, Pietro; Colonna, Cristiana; Melchers, Rutger C; et al. (British journal of dermatology, 2024)
Lymphomatoid papulosis (LyP) is a rare cutaneous T-cell lymphoproliferative disorder. Comprehensive data on LyP in the paediatric population are scarce.To characterize the epidemiological, clinical, histopathological and prognostic features of paediatric LyP.This was a retrospective multicentre international cohort study that included 87 children and adolescents with LyP diagnosed between 1998 and 2022. Patients aged ≤ 18 years at disease onset were included. LyP diagnosis was made in each centre, based on clinicopathological correlation.Eighty-seven patients from 12 centres were included. Mean age at disease onset was 7.0 years (range 3 months-18 years) with a male to female ratio of 2 : 1. Mean time between the onset of the first cutaneous lesions and diagnosis was 1.3 years (range 0-14). Initial misdiagnosis concerned 26% of patients. LyP was most often misdiagnosed as pityriasis lichenoides et varioliformis acuta, insect bites or mollusca contagiosa. Erythematous papules or papulonodules were the most frequent clinical presentation. Pruritus was specifically mentioned in 21% of patients. The main histological subtype was type A in 55% of cases. When analysed, monoclonal T-cell receptor rearrangement was found in 77% of skin biopsies. The overall survival rate was 100%, with follow-up at 5 years available for 33 patients and at 15 years for 8 patients. Associated haematological malignancy (HM) occurred in 10% of cases (n = 7/73), including four patients with mycosis fungoides, one with primary cutaneous anaplastic large cell lymphoma (ALCL), one with systemic ALCL and one with acute myeloid leukaemia. If we compared incidence rates of cancer with the world population aged 0-19 years from 2001 to 2010, we estimated a significantly higher risk of associated malignancy in general, occurring before the age of 19 years (incidence rate ratio 87.49, 95% confidence interval 86.01-88.99).We report epidemiological data from a large international cohort of children and adolescents with LyP. Overall, the disease prognosis is good, with excellent survival rates for all patients. Owing to an increased risk of associated HM, long-term follow-up should be recommended for patients with LyP.Lymphomatoid papulosis is a very rare skin condition caused by an abnormal increase in white blood cells (called ‘lymphocytes’) in the skin. The condition rarely affects children, so most of the scientific data published about this disease focuses on adults.This study involved 12 academic dermatology centres in Europe, the Middle East and North America, and gathered data from about 87 children who presented with symptoms of lymphomatoid papulosis before the age of 19 years. The aim of this study was to better describe this disease in the paediatric population and discuss its treatment options and evolution.We found that the presentation of the disease in children is roughly the same as in adults. Safe and effective treatment options exist. The disease is not life threatening, but it requires investigation by a dermatologist, both to make a careful diagnosis and to monitor it as sometimes associated cancers that originate from blood cells can occur, mostly on the skin.